Eletrificação rural: um estudo sobre o Programa Luz para Todos - Zimmermann, Beatrice Aline (2016)
The recent focus on the importance of infrastructure to growth and economic development combined with the importance given to the issue of poverty and its reduction have been causing discussions on rural electrification over the past few years. This relation, in theory, occurs through ways that involve objective economic factors that generally relate to increase of the productivity in places where the investment takes place. In these locations, theoretically, we should observe an increase in the range of private productive activities undertaken, since under these circumstances it is expected that productivity of the factors is greater. In addition to these routes, there are still other channels involving more subtle aspects of investment in electrification. In this sense, one can cite, for example, improvements related to education and health, ranging from extension of school activities to other shifts and the access to teaching tools before unviable, up to reductions in natality and mortality rates, related to better access to information and to improvements in the health facilities. Based on these statements, this study aims to contribute to the understanding of the importance of electrical infrastructure for people living in remote areas of the big cities of Brazil, using for it the Agricultural Census (1996 and 2006), the School Census (1997 to 2011), the health database (DATASUS, 2000 to 2010) and the program Luz Para Todos (LPT) of the federal government of Brazil, put in place in 2003. Overall, the results indicate the program increases the chances of rural establishments and rural schools have access to electricity. Moreover, the results show effects from electrification provided by the program on health and education issues. On the productive aspects, however, were not found significant effects.